Perakitan Alat Pengasin Telur Berdasarkan Prinsip Termos - Aji, Armadito Abilawa Cipta; Tamrin, Tamrin; Warji, Warji; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2022)
This study aims to manufacture, and test a machine to accelerate the process of salting eggs by immersing them in a 25% salt solution at a temperature of 60oC-65oC. In this study using the method of assemble, and test the performance of the tool. This egg salting machine consists of several parts including the outer tube, inner tube, nest, lid, and thermostat sensor hole and is equipped with a stove holder. This machine is capable of salting eggs such as duck/duck eggs, chicken eggs, and quail eggs with the principle of a thermos that uses an electric stove as a heater. This salting machine is capable of soaking duck/duck eggs, chicken eggs, and quail eggs in a salt solution of 25% at a temperature of 60-65oC. This machine is similar to a thermos that can maintain a temperature of 60-65oC for 3 hours, and can accommodate 120-133 duck eggs and chicken eggs, and 700-704 quail eggs in one soak. Keywods: Eggs, Mariners, Salting Machine, Temperature.